2009
DOI: 10.2131/jts.34.s43
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative work on evaluation of ovarian toxicity 3) Effects of 2- or 4- week repeated-dose toxicity and fertility studies with tamoxifen in female rats

Abstract: To assess whether ovarian histopathological examination in repeated-dose rodent toxicity study could reliably anticipate toxic effects on female reproductive function and to assess whether ovarian change could be detected in a 2-week repeated-dose toxicity study, tamoxifen was administrated orally to female rats at 0.005, 0.03, or 0.2 mg/kg/day for 2 and 4 weeks in the repeated-dose toxicity studies, and for 2 weeks prior to cohabitation, during cohabitation, and through Gestation Day 7 in a female fertility s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…PCNA immune-stained sections confirmed the similar numbers of small-and medium-sized follicles in TMX and control groups. Unchanged numbers of small follicles, which represent gonadotropin-insensitive primordial and primary follicles, accompanied by decreased numbers of pre-antral and antral follicles, as well as decreased numbers of corpora lutea, were observations that were common to all of the studies mentioned above (7)(8)(9)(10)(11). This suggests that TMX per se is not harmful for resting primordial and gonadotropin-insensitive small follicles.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…PCNA immune-stained sections confirmed the similar numbers of small-and medium-sized follicles in TMX and control groups. Unchanged numbers of small follicles, which represent gonadotropin-insensitive primordial and primary follicles, accompanied by decreased numbers of pre-antral and antral follicles, as well as decreased numbers of corpora lutea, were observations that were common to all of the studies mentioned above (7)(8)(9)(10)(11). This suggests that TMX per se is not harmful for resting primordial and gonadotropin-insensitive small follicles.…”
Section: Discussionmentioning
confidence: 82%
“…TMX exposure led to anovulation in the majority of rats in all but one study assessing estrous cycles-70% of TMX-exposed rats were anovulatory in the study by Donath and Nishino (8,9,11). Compared to controls, both absolute and relative ovarian weight was found to be significantly decreased following TMX exposure in all but one study (7)(8)(9)(10)(11). Similar to our findings, Matsuda et al (7) and Tsujioka et al (11) noted a decrease in the number and size of corpora lutea in TMX-treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-clinical data are not consistent: few studies have implied that the addition of tamoxifen to cyclophosphamide resulted in decreased follicle loss and improved reproductive function in rats (Kim et al 2010. Another toxicological study on rats that employed a higher dose of tamoxifen showed a disturbance of estrus cycle and a decrease in the number of pregnant rats that were considered to be related to ovarian histopathological changes (Tsujioka et al 2009). Two clinical studies indicate that tamoxifen may affect the follicular pool, resulting in a delayed fall in AMH in a group of patients receiving tamoxifen and goserelin.…”
Section: Tamoxifenmentioning
confidence: 99%
“…Reference: Tsujioka et al (2009) Primordial follicle damaging agents 4-vinylcyclohexene diepoxide (VCD) -1 -ess of apoptosis in small follicles Company: Toa Eiyo Ltd. Studies: Repeated toxicity study Animals: Sprague-Dawley rats (Slc:SD) rats Doses, route and duration: Intraperitoneally treatment at 5, 20 and 80 mg/kg once a day for 2-or 4-weeks in the repeated toxicity study.…”
Section: Mitsubishi Tanabe Pharma Corporationmentioning
confidence: 99%